(untitled) (Journal of the College of Education for Women, 2019)
There are many reasons made Basra a good defense, first of all was theestablishment of the famous Arab tribes, like Bakir bn. Wail and Tamim. Besides there wereA lot the armed forces. In addition to that the strategic place of Basra. All these reasonsplayed a good part when the war broke out.The Arabic tribes played a good part in the war to engaged Persians, and preventthem from sending any helps to their armies against the Kufain who were fighting Persians inthe North of Iraq. While the Basrain army aiming to Conquer the south of Iraq.Basra become the first strategic place for the Islamic movement of the conquers.Latter on Kufa and Bahrain were the second and third.The Muslims guranted the pupils of book their life, religion, posseasion and nointerferencein their religious affairs.